The little drummer girl - Le Carré, John, 1931-2020 (Penguin Books, 2011)
Israeli intelligence agent Kurtz--aka Schulman, aka Gold, aka Raphael--assembles a private army to trap the most dangerous Palestinian terrorist, a trap that perilously involves a brilliant, young English actress.